A methodology for discovering novel brain-relevant peptides: Combination of ribosome profiling and peptidomics. (February 2020) - Tharakan, Ravi; Kreimer, Simion; Ubaida-Mohien, Ceereena; Lavoie, Joelle; Olexiouk, Volodimir; Menschaert, Gerben; Ingolia, Nicholas T.; Cole, Robert N.; Ishizuka, Koko; Sawa, Akira; Nucifora, Leslie G.
Highlights: A new methodology to discover brain derived peptides is introduced. The methodology combines ribosome profiling and peptidomics. A peptide reported in peripheral tissues is found in brain tissues and cells. Abstract: Brain derived peptides function as signaling molecules in the brain and regulate various physiological and behavioral processes. The low abundance and atypical fragmentation of these brain derived peptides makes detection using traditional proteomic methods challenging. In this study, we introduce and validate a new methodology for the discovery of novel peptides derived from mammalian brain. This methodology combines ribosome profiling and mass spectrometry-based peptidomics. Using this framework, we have identified a novel peptide in mouse whole brain whose expression is highest in the basal ganglia, hypothalamus and amygdala. Although its functional role is unknown, it has been previously detected in peripheral tissue as a component of the mRNA decapping complex. Continued discovery and studies of novel regulating peptides in mammalian brain may also provide insight into brain disorders.